A humic acid-polyquaternium-10 stoichiometric self-assembled fibrilla polyelectrolyte complex: Effect of pH on synthesis, characterization, and drug release. Issue 11 (23rd July 2016) - Siyawamwaya, Margaret; Choonara, Yahya E.; Kumar, Pradeep; Kondiah, Pierre P. D.; du Toit, Lisa C.; Pillay, Viness
ABSTRACT: A polyelectrolyte complex (PEC) was produced and validated from humic acid and polyquaternium-10 using a solution-blend method. Humic acid was used based on its properties of encapsulating hydrophilic and hydrophobic drugs while polyquaternium-10 provided high swellability in aqueous media. PECs at varying pH values were prepared and characterized for their physicochemical properties. Efavirenz (model drug) was used to assess the performance of the PEC. Results revealed that drug-loading ranged between 11.9–23.91% and PEC formation was due to ionic reactions between the amino (polyquaternium-10) and carboxylic (humic acid) groups. This formed a fibrilla PEC complex that provided controlled release of efavirenz. GRAPHICAL ABSTRACT: